OP129 Predictors Of Effectiveness In Patients With Rheumatoid Arthritis. (12th January 2018) - dos Santos, Jéssica; Oliveira, Haliton; da Silva, Francisco Acurcio Michael; Almeida, Alessandra; Rodrigues, Flávia; Guerra, Augusto; Bennie, Marion; Godman, Brian; Alvares, Juliana
Abstract : INTRODUCTION: Biological disease-modifying anti-rheumatic drugs (bDMARDs) have become firmly established in the management of patients with rheumatoid arthritis (RA), but some patients do not improve despite therapy. This study evaluated the predictors of effectiveness of the bDMARDs on a cohort of patients with rheumatoid arthritis (RA) in the Brazilian Public Health System. METHODS: RA individuals treated with bDMARDs, were included in the open prospective cohort study. The Clinical Disease Activity Index (CDAI) was used to assess the effectiveness comparing results at baseline and after 6 months of follow-up. The association between socio-demographic and clinical characteristics with the disease activity measured by the CDAI was also investigated. The bDMARDs was considered effective when the patient achieved remission or low disease activity and considered not effective when there was still moderate or high disease activity. Pearson's chi-square was applied for the univariate analysis to evaluate the association of effectiveness measured by the CDAI with the socio-demographic (gender, education, marital status and race) and clinical variables (type of drug, EuroQol (EQ)-5D and Health Assessment Questionnaire (HAQ)). Logistic regression was applied in the multivariate analysis of the variables that presented a p< .20 value during the univariate analysis. RESULTS: All 266 RA patients completed six months of follow-up. The most widely used bDMARDs was adalimumab (57.1 percent), with etanercept used by 22.2 percent, golimumab by 7.5 percent, abatacept by 4.5 percent, tocilizumab by 3.4 percent, infliximab by 2.6 percent, certolizumab by 1.5 percent, and rituximab by 1.1 percent. The bDMARDs reduced disease activity as measured by CDAI at six months of follow-up (p<.001). The percentage of patients achieving remission or low disease activity was 40.6 percent. bDMARDs were more effective in patients with better functionality (Odds Ratio, OR = 2.140 / 95 percent Confidence Interval, CI 1.219 - 3.756) at beginning of treatment and in patients who not had a previous bDMARDs (OR = 2.150 / 95 percent CI 1.144 - 4.042). CONCLUSIONS: In this real-world study, functionality and use of previous bDMARDs are predictors in patients with RA treated with bDMARDs.